THE EFFECT OF E-BOOK USE, DIGITAL LITERACY AND AVAILABILITY OF LIBRARY BOOK COLLECTIONS ON LEARNING ACHIEVEMENT - Maksum, Maharani Pratiwi; Najmudin, Najmudin; Sunarko, Bambang (Soedirman Economics Education Journal, 2023)
Digitalization changes the world of education starting from teaching methods that follow trends, subject matter that follows world developments and ultimately being able to produce output that is in accordance with the situation and conditions of the employment field. The level of success can be seen from the student achievement. Learning achievement is influenced by two factors, both internal and external factors. This study aims to analyze (1) the effect of using e-books on learning achievement (2) the effect of digital literacy on learning achievement (3) the effect of book collection availability on learning achievement. This research is a quantitative study using a survey method. The population in this study were 141 students of Economic Education class 2016-2018. This sampling technique uses probability sampling. The data analysis technique used is multiple linear regression analysis and the result showed that the use of e-books, digital literacy, and availability of book collections in the library partially has a positive and significant effect on learning achievement.